2014
DOI: 10.1016/j.virol.2013.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced IRES activity by the 3′UTR element determines the virulence of FMDV isolates

Abstract: A reverse genetics approach was used to identify viral genetic determinants of the differential virulence displayed by two field foot-and-mouth disease virus (FMDV) strains (A/Arg/00 and A/Arg/01) isolated in Argentina during the 2000-2001 epidemics. A molecular clone of A/Arg/01 strain and viral chimeras containing the S-fragment or the internal ribosome entry site (IRES) of A/Arg/00 in the A/Arg/01 backbone were constructed and characterized. The IRES appeared as a determining factor of the lower level of A/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…Previous data reported that the 3΄UTR stimulates IRES activity both in the viral RNA (37) or when placed at the 3΄ position of a reporter gene (27). In addition, direct RNA–RNA interactions between these distant regions of the viral genome have been shown in vitro (1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous data reported that the 3΄UTR stimulates IRES activity both in the viral RNA (37) or when placed at the 3΄ position of a reporter gene (27). In addition, direct RNA–RNA interactions between these distant regions of the viral genome have been shown in vitro (1).…”
Section: Resultsmentioning
confidence: 99%
“…The 3΄UTR is essential for aphthovirus replication (34) although there are controversial results in other picornaviruses (35,36). In the case of the foot-and-mouth disease virus (FMDV) IRES, internal initiation of translation was stimulated by the 3΄UTR (27,37), regardless of the coexpression of the L protease. Therefore, IRES activity was stimulated both in the presence or absence of proteolyzed eIF4G and PABP.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies support an active role for interactions between the 5 and 3 ends of the viral RNA in controlling picornavirus gene expression. For instance, PV IRES activity in neuronal cells was stimulated by the viral 3 UTR (Dobrikova et al, 2003), and the FMDV IRES was stimulated by its own 3 UTR (Garcia-Nunez et al, 2014;Lopez de Quinto et al, 2002), irrespectively of the presence of polyA tail and the coexpression of the L protease.…”
Section: Implications Of Long-range 5 -3 Viral Rna Interactions On Irmentioning
confidence: 99%
“…Previous studies have shown that the 5 0 UTR of the viral genome harbored the hepatitis C virus like (HCV-like) IRES element [4,19]. The IRES element is responsible for the internal initiation of translation of viral RNA [20]. Thus, the plasmid pSK-D5 0 UTR was used as a negative control corresponding to a reduction in Fluc activity.…”
Section: Discussionmentioning
confidence: 99%